(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2024)
Tsunamis, wave triggered by underwater earthquakes or volcanic eruptions, can achieve significant run-up heights upon reaching shore. Run-up refers to the maximum vertical distance a tsunami wave reaches above the normal sea level. This study employs a numerical model to simulate the run-up wave at Canti Beach, South Lampung Regency, during the 2018 Sunda Strait tsunami. The method approximates solutions to the shallow water model consisting of mass and momentum conservation equations using the finite difference method in staggered grid grids and incorporates the upwind method for nonlinear terms. Bathymetry data from GEBCO was projected in two dimensions using the haversine formula. The numerical scheme includes a wet-dry procedure for simulating run-up waves. Results indicate that waves with a 60-second period and 0.09-meter amplitude create a 40.0195-meter inundation area, although this amplitude is significantly lower than the observed data from the 2018 Sunda Strait tsunami. Additionally, a simulation with a 0.1-meter amplitude results in a 1.8299-meter run-up height, closely matching the observed data. This study demonstrates that nonlinear shallow water equations can effectively estimate run-up height and inundation area at Canti Beach.